INTERNATIONAL LEGAL REGULATION OF INTERNATIONAL COMMERCIAL ARBITRATION (MULTILATERAL AND BILATERAL AGREEMENTS IN THE FIELD OF COMMERCIAL ARBITRATION) - Mamutova Aziza Axmetovna; Nizamova Iroda Eldorjon qizi; Mardonov Amir Sherzod o’g’li; Imamalieva Diyora Imamalievna (Scholar Express Journals, 2023)
This article delves into the international legal regulation of international commercial arbitration and the various multilateral and bilateral agreements that govern this field. The paper examines the enforcement and recognition of arbitral awards, the selection of arbitrators, and the role of international organizations in promoting international commercial arbitration. It also discusses the challenges faced in implementing these agreements and the potential for future developments in this area, in addition provides a succinct analysis of the crucial role of international legal regulation in facilitating international trade and commerce through commercial arbitration.
Keywords: international; regulation; convention; sources